Pengembangan Sistem Informasi Pemesanan Barang Berbasis Web - Suprianto, Arman (PT. Tech Cart Press, 2024)
Ordering goods is an important process in business activities that involves requesting or purchasing a product from a supplier of goods, both for personal and operational purposes of the company. The main problem in the goods order information system is the lack of efficiency and accuracy in data management and order processing. Often, these systems face errors in data input, such as stock information that is not updated in real-time, which can lead to mismatches between the availability of goods and customer orders. In addition, non-optimal system integration can slow down the ordering process, especially if it involves multiple departments or manual verification stages. An order information system is a technology solution designed to manage and automate the process of ordering goods effectively and efficiently. This research aims to design and develop a web-based goods ordering information system that is able to meet the needs of modern businesses, with a focus on ease of use, data security, and scalability to support the company's future growth. The development of a web-based goods ordering information system is an effort to create a digital platform that facilitates the process of managing goods orders efficiently, flexibly, and integrated. This system is designed to support various needs, such as order submission, stock availability checking, shipment status tracking, and real-time transaction data management. The test results of the web-based ordering information system have been tested on 10 main features, and all features have successfully met the expected results. Thus, the success rate of the testing of the web-based goods ordering information system shows a test success rate of 100%, which indicates that the system has functioned according to the needs and specifications that have been determined.